Supported Cu catalysts for the hydrogenation of furfural in aqueous phase: effect of support. Issue 3 (6th April 2017) - Wang, Yuan; Zhu, Wei; Sang, Shengya; Gao, Lijing; Xiao, Guomin
Abstract: Aqueous‐phase processing of biomass‐derived furfural is one of the promising ways to convert biomass into useful chemicals. Supported metal catalysts are crucial in the aqueous‐phase hydrogenation of furfural. Understanding the effect of acid and basic properties of supports on the performance of the catalysts will help understand the reaction pathways and develop more efficient catalysts. Here, a series of Cu‐based catalysts with different supports (Al2 O3, ZnO, SiO2, MgO, and ZSM‐5) have been investigated in hydrogenation of furfural in aqueous phase. The properties of the supports have been characterized by X‐ray diffraction, N2 adsorption–desorption, transmission electron microscope, H2 temperature‐programmed reduction, and CO2 and NH3 temperature‐programmed desorption. The results show that pure acid support leads to the formation of oligomers and pure basic support results in furfuryl alcohol as the main product. And the mass balance in reaction system catalyzed by Cu‐based catalysts with higher acidity amount is lower. © 2017 Curtin University of Technology and John Wiley & Sons, Ltd.